PENGARUH LINGKUNGAN KERJA DAN STRES KERJA TERHADAP PRODUKTIVITAS KERJA PADA KARYAWAN PT. INDONESIA EPSON INDUSTRY - Riris Marito Manullang; Wachid Hasyim; Riski Eko Ardianto (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
This study aims to analyze empirical evidence of the effect of work environment and work stress on work productivity of employees of PT. Indonesia Epson Industry. This study uses a quantitative method with a sample of 80 respondents, the sampling technique uses a non-probability sampling technique with purposive sampling category. The analytical method used in this research is the data/instrument quantity test, classical assumption test and hypothesis testing with the help of SPSS 25 software as a tool to analyze. The results showed that there was a positive influence on the work environment variable on the work productivity variable, while the work stress variable had no effect on work productivity so that only one independent variable had an effect on work productivity and one independent variable had no effect.